Not Evidence for Baumol's Cost Disease. A Reply to Atanda and Reed (International Journal for Re-Views in Empirical Economics, 2020) - Jochen Hartwig (International Journal for Re-Views in Empirical Economics (IREE), 2020)
In this article Jochen Hartwig replies to Antanda's and Reed's replication study published earlier this year (IREE, 2020-1).
Keywords: I11; J30; E24; 330; Baumol's cost disease; Health care expenditure; Replication study